Membangun Kesetaraan Gender Dalam Kehidupan Keluarga Perspektif Hukum Islam - Muchammad Qosim Alfaizi (UIN Sunan Kalijaga Yogyakarta, 2022)
This paper aims to strengthen opinions or concepts about building gender equality in family life. This paper is a qualitative study of a number of data sources (works); books and articles that discuss building gender equality in the family. This research is included in the category of further research on the same object of study, namely about building gender equality in family life. In addition, there has not been any previous research that describes building gender equality in family life which is then analyzed using Islamic law. The results of the study indicate that building gender equality in family life in order to form a prosperous family is throughgender partnershipsin the family. Then, build gender equality throughgender partnershipin family life in line with Islamic law. This is because so as not to cause damage in the form of not carrying out family functions.